[U(bipy)4]: A Mistaken Case of U0?. Issue 6 (7th January 2016) - Fortier, Skye; Veleta, José; Pialat, Amélie; Le Roy, Jennifer; Ghiassi, Kamran B.; Olmstead, Marilyn M.; Metta‐Magaña, Alejandro; Murugesu, Muralee; Villagrán, Dino
Abstract: After more than 50 years, the synthesis and electronic structure of the first and only reported "U 0 complex" [U(bipy)4 ] (1 ) has been reinvestigated. Additionally, its one‐electron reduced product [Na(THF)6 ][U(bipy)4 ] (2 ) has been newly discovered. High resolution crystallographic analyses combined with magnetic and computational data show that 1 and its derivative 2 are best described as highly reduced species containing mid‐to‐high‐valent uranium ligated by redox non‐innocent ligands. Abstract : U bet your bipy : Lost to time but not forgotten, the first reported and isolable "U 0 " complex [U(bipy)4 ] has been synthesized and reinvestigated (see figure; bipy=2, 2′‐bipyridine). Through a thorough investigation, definitive oxidation state assignments have been made. [U(bipy)4 ], along with its reduced product [Na(THF)6 ][U(bipy)4 ], are revealed to be highly reduced species with U‐centers in mid‐to‐high oxidation states.